PENERAPAN MODEL PROJECT BASED LEARNING DALAM PENULISAN CERPEN SMP NEGERI 18 LAU, KABUPATEN MAROS - I Nani, I Nani; Nurhayati, Nurhayati; Hasjim, Munirah (Universitas Hasanuddin, 2018)
This research aimed (1) to explain the learning process in writing short stories using the Learning-Based Project Methode by Class VIII at Lau State Junior High School, Maros Regency; (2) to explain the learning tesult of the short stories after the implementation of the model of the Learning-Based Project Methode by Class VIII at Lau State Junior High School, Maros Regency.The research type used was the Classroom Action Research, know as Penelitian Tindakan Kelas (PTK) or the Classroom Action Research. This Classroom Action Research implemented several cyrcle in its implementation.The research results indicated that there had been inceases of the process and the learning achievement of the students. Meanwhile, the learning result of the control class showed a difference. Cycle I reached the mean result of 70,86 and the cycle II reached the mean value of 72,11. However, such difference did not show any increase in the learning result. Both cycle could be categorized as adequate. The learning achievement of the experiment class showed a difference which was significant enough. Cycle I reached the mean value of 79,76 and could be categorized as adequate, while cycle II reached the mean value of 84,79 which was categorized as good. This revealed the learning increase which was significant enough.